1998
DOI: 10.1007/s001340050563
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory failure caused by secondary alveolar proteinosis in a patient with acute myeloid leukemia: a case report

Abstract: Pulmonary alvelolar proteinosis (PAP) is a rare cause of chronic respiratory failure due to progressive alveolar accumulation of a periodic acid-schiff (PAS) positive proteinaceous material. In some cases, the rapid accumulation of intra-alveolar material leads to acute respiratory failure (ARF). We report the causative role of secondary PAP in the case of a 26-year-old man with acute myeloid leukemia who developed fever, increased serum lactate dehydrogenase level and ARF, and required mechanical ventilation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Hematologic malignancies, predominantly myelogenous leukemias are well established causes. [59][60][61][62] This observation is supported by the resolution of pulmonary process after the restoration of normal hematopoietic function. 63 Immunodeficiency disorders such as thymic alymphoplasia, 64 and IgA deficiency, 65 or acquired states such as solid organ transplantation, 66 treatment with imatinib mesylate 67 and acquired immune deficiency syndrome 68,69 have been associated with PAP.…”
Section: Secondary Papmentioning
confidence: 73%
“…Hematologic malignancies, predominantly myelogenous leukemias are well established causes. [59][60][61][62] This observation is supported by the resolution of pulmonary process after the restoration of normal hematopoietic function. 63 Immunodeficiency disorders such as thymic alymphoplasia, 64 and IgA deficiency, 65 or acquired states such as solid organ transplantation, 66 treatment with imatinib mesylate 67 and acquired immune deficiency syndrome 68,69 have been associated with PAP.…”
Section: Secondary Papmentioning
confidence: 73%
“…Although neutralizing antibodies to GM-CSF are present in patients with primary PAP, 14,30,31 and secondary PAP has been linked to AML, 32,33 CML 34 and MDS, 35,36 the prevalence of these antibodies among leukemia patients and their biological link to myeloid leukemia is unknown. Kitamura et al 14 showed that anti-GM-CSF IgG, but not IgM or IgA, are present in patients with PAP and may be pathogenic in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…89 Approximately 10 -30% of patients are asymptomatic at presentation, 9,14,90 whereas others present acutely with rapid progression to respiratory failure. [91][92][93][94][95] Acute and rapid progression can occur because of infection. 12 Pneumothorax and cor pulmonale occur rarely.…”
Section: Clinical Featuresmentioning
confidence: 99%